Smart dispenser based on the Internet of Things - Windy Aria; Oriza Candra (Journal of Industrial Automation and Electrical Engineering, 2025)
Human health is highly dependent on adequate daily fluid intake. Unfortunately, public awareness of monitoring water consumption remains low. This research aims to design and build an Internet of Things (IoT)-based smart dispenser capable of automatically and personally recording and monitoring water consumption. This system uses an RFID sensor to identify the user, an infrared sensor to detect the presence of a glass before filling it, and a water flow sensor to measure the volume of water consumed. Each user's water consumption data is sent and recorded in a Google Spreadsheet, and the desired volume of water can be adjusted in the Blynk application. Test results show that the system can work effectively in recognizing the user, controlling the water flow according to the set volume, and transmitting data accurately to the IoT platform. This tool is expected to raise awareness of the importance of body hydration and support digital health monitoring in homes, schools, offices, and healthcare facilities